2022
DOI: 10.1177/09731849221083732
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parental School Choice in Varied Socio-economic Milieus: A Case Study of a Village in Punjab

Abstract: With the upsurge of private schools, parents are struggling with a variety of schooling options. Given the exclusionary nature of privatisation, the market has led to the reproduction of social inequality amidst a plurality of choice. By mapping the school choice process, the article aims to explore school choice in the varied socio-economic milieu in a village in Punjab. Based on the qualitative data collected with the help of semi-structured interviews and focus group discussions (FGDs), the study draws link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the present scenario, some studies found that the majority of the parents preferred to send their wards to English medium schools for their reputation, quality education and for their ability to impart English-speaking skills in the students (Galab et al. , 2013; Narwana, 2017). In sum, the child's future success and career prospects were important considerations for the parents' school choice decision as it helps the child to achieve upward mobility in society (Donner, 2005; Nambissan, 2009).…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…In the present scenario, some studies found that the majority of the parents preferred to send their wards to English medium schools for their reputation, quality education and for their ability to impart English-speaking skills in the students (Galab et al. , 2013; Narwana, 2017). In sum, the child's future success and career prospects were important considerations for the parents' school choice decision as it helps the child to achieve upward mobility in society (Donner, 2005; Nambissan, 2009).…”
Section: Literature Reviewmentioning
confidence: 90%
“…Moreover, the quality and qualification of teachers, as well as teacher credentials and teaching pedagogy, were found to be essential considerations throughout the school selection process (Lahoti and Mukhopadhyay, 2019;Kar and Sinha, 2021). In the present scenario, some studies found that the majority of the parents preferred to send their wards to English medium schools for their reputation, quality education and for their ability to impart English-speaking skills in the students (Galab et al, 2013;Narwana, 2017). In sum, the child's future success and career prospects were important considerations for the parents' school choice decision as it helps the child to achieve upward mobility in society (Donner, 2005;Nambissan, 2009).…”
Section: Studies In Indiamentioning
confidence: 93%
“…Digital amenities such as an available functional computer and internet access are other key variables that determine the enrollment of students in a school. Amenities, both physical and digital, are necessary and often a deciding factor for parents to choose the school for their children (Hill, Samson, and Dasgupta 2011;Kim, Yi, and Hong 2021;Narwana and Gill 2022).…”
Section: Methodsmentioning
confidence: 99%